#TITLE_ALTERNATIVE# - SYAFITRI ( NIM 2511301 ), AMELIA
Land cover change in area with high population assign great effect in global activity and economy changes. Rapid industrial development in several regions in Indonesia have an impact on the pattern of land use and land cover. Land cover change in particular location and period of time, can be researched as a phenomenon or dichotomous event. Binary logistic regression is a regression model with binary or dichotomous response variabel. The result of binary logistic regression is determined by binary classification or classified based on the threshold value. The selection of threshold value is giving large effect on model accuration. The approach to determine threshold value can be seen through overall accuracy. The results of this study indicate that threshold value from partial binary logistic regression analysis generate better overall accuracy. This means this method give significant effect with diverse characters on the probability of land cover change. Meanwhile, overall regression analysis generate smaller overall accuracy than partial analysis